A Unique B-Family DNA Polymerase Facilitating Error-Prone DNA Damage Tolerance in Crenarchaeota - Feng, Xu; Liu, Xiaotong; Xu, Ruyi; Zhao, Ruiliang; Feng, Wenqian; Liao, Jianglan; Han, Wenyuan; She, Qunxin (Frontiers in Microbiology, 2020)
Sulfolobus islandicus codes for four DNA polymerases: three are of the B-family (Dpo1, Dpo2, and Dpo3), and one is of the Y-family (Dpo4). Western analysis revealed that among the four polymerases, only Dpo2 exhibited DNA damage-inducible expression. To investigate how these DNA polymerases could contribute to DNA damage tolerance in S. islandicus, we conducted genetic analysis of their encoding genes in this archaeon. Plasmid-borne gene expression revealed that Dpo2 increases cell survival upon DNA damage at the expense of mutagenesis. Gene deletion studies showed although dpo1 is essential, the remaining three genes are dispensable. Furthermore, although Dpo4 functions in housekeeping translesion DNA synthesis (TLS), Dpo2, a B-family DNA polymerase once predicted to be inactive, functions as a damage-inducible TLS enzyme solely responsible for targeted mutagenesis, facilitating GC to AT/TA conversions in the process. Together, our data indicate that Dpo2 is the main DNA polymerase responsible for DNA damage tolerance and is the primary source of targeted mutagenesis. Given that crenarchaea encoding a Dpo2 also have a low-GC composition genome, the Dpo2-dependent DNA repair pathway may be conserved in this archaeal lineage.